Intraoral Myeloid Sarcoma with Bilateral Involvement - Case Report - Poulopoulos Athanasios; Iordanidis Fotios; Andreadis Dimitrios; Antoniadis Konstantinos (Balkan Journal of Dental Medicine, 2017)
Background: Myeloid sarcoma (MS) is a solid malignant tumour associated with infiltration of immature myeloid precursor cells in an extramedullary site. The term MS has replaced the term granulocytic sarcoma and chloroma, which were used in the past. MS in the oral cavity is very uncommon, with less of 40 cases reported until recently. Case Report: We report the first case, the features, and the diagnostic sequence, of intraoral MS with bilateral palatal involvement, which presented as an initial manifestation, and preceded the appearance of acute myeloid leukaemia (AML). Diagnostic confirmation of such oral mucosal lesions usually requires biopsy, histopathological examination with additional immunohistochemical investigation. MS can occur during the course of acute or chronic myelogenous leukaemia, and myelodysplastic syndromes. In the vast majority of the reported cases, only one site was involved with a single intraoral MS lesion, and the cases predominantly associated with AML. Conclusion: The majority of intraoral MS occurs in patients with known AML, but in some of them, presented as an initial manifestation, and preceded the appearance of the disease. Therefore, clinicians should carefully evaluate all unusual oral lesions of unknown origin.